Effect of unilateral dynamic stability on lateral jump performance in team sport athletes - Lockie, R. G.; Schultz, A. B.; Luczo, T. M.; Callaghan, S. J.; Jeffriess, M. D. (Serbian Journal of Sports Sciences, 2013)
This study investigated the interaction between dynamic stability, as measured by unilateral functional reach in the Star Excursion Balance Test (SEBT), and lateral jump distance for each leg in 16 male team sport athletes. The SEBT measured reach distances in 8 directions (anterior, anterolateral, lateral, posterolateral, posterior, posteromedial, medial, anteromedial). Pearson`s correlation analysis (p </= 0.05) determined relationships between SEBT excursions and left and right leg lateral jump distance. A stepwise multiple regression analysis (p </= 0.05) determined excursions that predicted lateral jump performance. Reaches in the lateral, posterolateral, posterior, posteromedial, and medial directions were significantly correlated with greater jump distances for each leg (r = 0.514 - 0.823). Right leg posteromedial and posterior reach (left stance leg) predicted the left leg lateral jump (r = 0.936; r2 = 0.877). Right leg lateral and anterolateral reach (left stance leg) predicted the right leg lateral jump (r = 0.867; r2 = 0.751). Relationships between dynamic stability as measured by the SEBT, and maximal lateral jumping, were established. This is likely due to similarities in joint movements and muscle involvement. The effect of dynamic stability was particularly noticeable for the dominant leg in a lateral jump, which was the left leg in this study.